1987
DOI: 10.1007/bf00025645
|View full text |Cite
|
Sign up to set email alerts
|

Progress in cohort cultures of aquatic Oligochaeta

Abstract: Our laboratory work on the life cycle of aquatic Oligochaeta has been extended to the tubificids Potamothrix hammoniensis and P heuscheri, as well as to the lumbriculid Bichaeta sanguinea.Basically we measured the duration of the time required for the embryonic development inside the cocoons, at different temperatures. In addition, cohorts of these species were cultured and the time required to attain the sexual maturation and the cocoon laying stages were estimated.The results concerning these three species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Laboratory cultures studied by various research groups indicate that growth rate and time until reproduction can vary over a wide range (Bonacina et al, 1987(Bonacina et al, , 1989Paoletti, 1989;Poddubnaya, 1980;Timm, 1974cited in Poddubnaya, 1980. Data obtained from field observations showed different peaks of abundance in eutrophic as well as in oligotrophic freshwater habitats (Milbrink, 1973(Milbrink, , 1978(Milbrink, , 1983Reynoldson, 1983;Saether, 1980;Sarkka & Aho, 1980;Sarkka, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory cultures studied by various research groups indicate that growth rate and time until reproduction can vary over a wide range (Bonacina et al, 1987(Bonacina et al, , 1989Paoletti, 1989;Poddubnaya, 1980;Timm, 1974cited in Poddubnaya, 1980. Data obtained from field observations showed different peaks of abundance in eutrophic as well as in oligotrophic freshwater habitats (Milbrink, 1973(Milbrink, , 1978(Milbrink, , 1983Reynoldson, 1983;Saether, 1980;Sarkka & Aho, 1980;Sarkka, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…6B). The ineffective control was also due to the temporal delay between the time of high egg population density in the culture and the time of a possible reduction in ovigeration percentage (at least 100 days at 20 "C, Bonacina et al, 1987a).…”
Section: Resultsmentioning
confidence: 99%
“…Each mass culture was kept at 20 "C in a 6 cm wide cylindrical glass jar and inspected fortnightly; at every control check the animals were counted according to the biological stage (E = eggs + embryos; Y = youngs; M = mature, but not ovigerous; 0 = ovigerous, i.e. with eggs in the ovisac) and 1 g (wet weight) of deep-frozen lettuce added to the sand (for more culturing details, see Bonacina et al, 1987a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9) is roughly 105 to 127 days. Bonacina et al (1987 , Table 1) estimated the corresponding time for a number of freshwater lumbriculids and tubiticids in 10 ' C and 15 ' C to be 25 to 100 and 16.5 to 62.7 days, respectively. Brinkhurst (1964), in his study of Tubifx costatus found that cocoons started to occur in the samples in early May, to be replaced by newly hatched juveniles in early July, which would indicate that the embryonic development can be completed in 1 to 2 months in that species.…”
Section: Reproductionmentioning
confidence: 99%